Industrial economy framework of maximizing energy efficiency in agricultural systems - Najimov Iskander; Adilbaev Ismail; Kamalov Maqset; Azirbaev Babur (BIO Web of Conferences)
The current situation of energy consumption in agricultural systems and the problems existing in traditional farming practices are proposed to achieve higher energy efficiency, lower environmental impact, and improved economic viability. This paper aimed to develop a comprehensive framework that integrates principles of the industrial economy with agricultural practices to achieve significant energy savings. To meet the increased sustainability and productivity demands of modern agricultural enterprises, the capability of energy management systems must improve. One important technique for doing this is to redesign energy allocation frameworks, the optimization models that agricultural stakeholders follow to perform resource distribution and efficiency assessments. In this study, the Analytical Hierarchy Process (AHP) method in agricultural energy efficiency evaluation combines the decision-support system method based on multi-criteria analysis, comparative weighting techniques, and hierarchical structuring. The research results show that the constructed model can systematically analyze the comparative effectiveness of energy-efficient strategies, and renewable energy integration is more economically viable, more environmentally sustainable, and more operationally efficient in agricultural energy management. Analyzing this energy optimization trend reveals that solar energy adoption has been the largest contributor to sustainable energy transition in agriculture, with drip irrigation systems and biomass energy solutions (e.g., solar-powered irrigation, wind-assisted grain drying) leading the way, but that traditional fossil-fuel-based farming machinery has faded in recent decades.